A Study of Linguistic Landscape in Papaya Supermarket - Maghfira Muliasani, Raudya; Haryati, Haryati (Ethical Lingua: Journal of Language Teaching and Literature, 2026)
This study focuses on the sociolinguistic study of the linguistic landscape in Papaya Supermarket. This study's objectives are to identify and classify the signs based on language display and function found in Papaya Supermarket. The writer utilizes Landry & Bourhis' (1997) theory of linguistic landscape and uses a descriptive-qualitative approach to analyze the data textually. The data consists of 73 signs. Then, the writer classifies the data based on the language display: monolingual, bilingual, and multilingual. Monolingual signs consist of 21 signs, bilingual signs consist of 32 signs, and multilingual signs consist of 20 signs. The languages that the writer has found consist of Indonesian, English, and Japanese. The function of these languages is classified by the writer into two: informational function and symbolic function. The informational function consisted of 67 signs, and the symbolic function consisted of 6 signs. The primary function of language is to convey information, as seen in signs that guide, prohibit, or inform everyone. Language, on the other hand, serves as a symbol in advertisements and products from other countries that use foreign words to evoke a specific emotion.